Mechanisms of Submarine Debris Flow Growth. Issue 3 (23rd March 2022) - Du, Jianting; Choi, Clarence Edward; Yu, Jiantao; Thakur, Vikas
Abstract: Submarine debris flows are among the largest types of landslide on planet Earth. They occur under the cloak of the sea so little is known about how they reach such large volumes. Field evidence suggests that the entrainment from the sediment‐rich sea floor enables the growth of submarine debris flows. However, there is a dearth of understanding of the dynamic processes of entrainment. In this study, a new entrainment model is proposed for submarine debris flows with different clay contents. The entrainment model considers the relative contributions from basal grain friction and fluid viscous stresses that drive the entrainment process, and the effects of hydroplaning. To evaluate the new model, a new experimental setup is developed to simulate submarine debris flows, with clay contents from 4% to 12%, overriding and entraining a loose sand bed. The clay content is found to have profound effects on the entrainment dynamics. Flows with high clay contents (i.e., ≥10%) hydroplane, which enhances the mobility of the flow but reduces its entrainment potential. The predicted entrainment depths from the proposed model are consistent with the measured ones from the experiments. The proposed theoretical model and unique experimental evidence can be used as guiding tools to progress toward the inclusion of entrainment in vulnerability assessments of offshore infrastructure. Plain Language Summary: Submarine debris flows are among the largest mass movements of soil on planet Earth and pose a significant threat to offshore infrastructure. A key mystery that remains unsolved is understanding the means by which these flows grow to such large volumes. In this study, we propose a new theoretical model to describe the entrainment of a sand bed by submarine debris flows with different clay contents. The theoretical model also considers the effects of hydroplaning, which is the process by which a thin film of water is sandwiched between the flow head and seafloor to provide a cushion for the flow to ride on to reduce basal friction and enable long travel distances. To evaluate our proposed theoretical model, we use a newly developed experimental setup to produce unique data by simulating submarine debris flows overriding and entraining a loose sand bed. We conclude that our proposed theoretical model provides consistent predictions of the measured entrainment depths from the experiments. The proposed theoretical model and unique experimental evidence can be used as guiding tools to progress toward the inclusion of entrainment for vulnerability assessments of offshore infrastructure. Key Points: Experimental evidence reveals for the first time the mechanisms of sand bed entrainment by submarine debris flows with varying clay contents A new entrainment model with consideration of the effects of hydroplaning is proposed, and shown to be consistent with experimental results The clay content of a submarine debris flow has profound effects on its entrainment dynamics